Chapter 13 Interaction and Risk Management in Shared Leadership - Wadel , Carl Cato (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The chapter presents a case from a government agency in Norway, where two assistant directors share a leadership position and must interact extensively. The main purpose is to highlight some benefits and challenges related to shared leadership when it comes to risk prevention and handling unforeseen events. The analysis is based on a relational perspective that emphasizes that successful interaction between people requires complementary skills, conceptualized as relational skills. The chapter concludes that the patterns of interaction and relational skills that develop during shared leadership can help prevent undesirable events. This is partly because shared leadership can provide increased capacity in identifying risks. Common experiences in handling risks and unforeseen events may contribute to learning that in turn provides the potential for further development of the interactional and relational skills in shared leadership. At the same time, shared leadership entails some risks that may impact on the prevention and handling of such events. For instance, interactional challenges that may arise in a shared leadership may prevent leaders from discovering potential hazards."